Financial Marketing in E-Commerce: How Trust, Transaction Ease, and Information Quality Shape Online Purchase Decisions - Andi Muara Arumbarkah (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines how trust, transaction ease, and information quality influence online purchase decisions among young adult e-commerce users. Research Method: A quantitative explanatory survey was conducted with 64 eligible users recruited from a private university setting in Makassar, Indonesia. All respondents had prior purchasing experience on the focal marketplace platform. Trust, transaction ease, information quality, and online purchase decision were measured using multi-item five-point Likert scales. The analysis employed item-total validity assessment, Cronbach’s alpha, classical regression diagnostics, multiple linear regression, t-tests, an overall F-test, and the coefficient of determination using SPSS. Results and Discussion: The findings support a transaction-centered explanation of e-commerce behavior. Consumers are more willing to decide to purchase when they trust the exchange environment, perceive the transaction process as easy, and receive information that is sufficiently accurate, timely, relevant, and complete. Ease and trust display almost identical standardized coefficients, indicating that process convenience and transaction confidence should be regarded as joint priorities rather than as competing explanations. Information quality has a smaller unique effect but remains an important part of the purchase-conversion environment. Implications: Marketplace managers should reduce transactional friction, protect trust through reliable seller and platform signals, and improve the accuracy, relevance, timeliness, and completeness of product information. Originality: The study integrates Technology Acceptance Model logic, e-commerce trust, and information quality theory into a single conversion-oriented framework and compares their relative effects within a tightly defined segment of young adults.